Perioperative Management of Intradural Extramedullary Tumor Patients Undergoing Hemilaminectomy and Tumor Resection: A Case Report - Oka Rastini, Luh Ratna; Made Septyana Parama Adi (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Intradural extramedullary (IDEM) tumor is a benign neoplasm originating in the spinal canal and accounts for approximately two-thirds of cases of primary spinal tumors. This case report aimed to further discuss the anesthetic management of IDEM tumor patients who underwent hemilaminectomy and tumor resection. Case presentation: A 25-year-old woman came with complaints of right hemiparesis, hypoesthesia as high as L3-L4, and unable to hold back urination since 4 months ago. Magnetic resonance imaging (MRI) examination showed a heterogeneous intradural extramedullary solid mass in the central spinal cord as high as Th 10-11 posterior, which narrowed the spinal canal. Dextra hemilaminectomy, tumor resection, and unilateral stabilization of dextra Th10-12 fusion were performed under general anesthesia and thoracolumbar interfascial plane blocks (TLIP). General anesthesia with non-kinking endotracheal intubation, controlled ventilation, and prone position is required for spinal thoracic surgery in adult patients. Propofol is a good induction agent, especially in maintaining the depth of anesthesia, because it can prevent side effects that arise from inhalation anesthetics. Conclusion: Bilateral modified TLIP block was performed in patients after induction of anesthesia with a median approach and ultrasonography (USG) guidance. TLIP block can reduce cumulative opioid consumption, acute pain intensity, the need for rescue analgesia, and the incidence of nausea and vomiting.